Gas sensors for sustainable and safe integrated gasification-FC system. (7th December 2017) - Pallozzi, V.; Zaza, F.; Di Carlo, A.; Bocci, E.; Carlini, M.
Abstract: Sustainability, safety and optimization of gasification systems for hydrogen production are strictly correlated to efficient monitoring devices and chemical gas sensors based on perovskite materials represent a very attractive technology for this purpose. The aim of this work is to evaluate sensing performances of LaFeO3 based materials for the application in integrated gasification-FC systems and their possible enhancements thanks to titanium partial substitution. Two perovskites, LaTi0.4 Fe0.6 O3 and LaFeO3, were therefore prepared via auto-combustion synthesis and tested in a bench scale reactor for CO, H2 and H2 S exposures. Synthesis parameters were properly defined and set to Φ = 0.45, CA/M = 2.5 and pH = 7. Transition of conductive behaviour (from p- to n-type) was observed. Titanium partial substitution provided higher sensitivity to CO at higher temperatures. Sensitivity to H2 was greater for unsubstituted material, but titanium presence assured chemical and thermal stability. During H2 S tests, instead, irreversible reaction with materials occurred compromising sensing performances. Highlights: Chemoresistive gas sensors for biomass gasification to fuel cell system control. An innovative perovskite material for high temperature CO, H2 and H2 S measurements. Titanium partial substitution on LaFeO3 based material was investigated. Improved chemical and thermal stability under reducing atmosphere. CO sensitivity enhanced up to 1.9 at higher temperatures.